HR Strategies for Enhancing Employee Performance in the Digital Age - Izaak, Fitri Devi Lestari (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Implementing artificial intelligence (AI)-based employee development strategies has great potential in improving individual and collaborative performance in the workplace. In the context of human resource management (HR), AI is used to optimize recruitment, training, performance evaluation and career development processes. Through a comprehensive literature review, this study identifies various AI methods used in employee development, including machine learning, deep learning, natural language processing, computer vision, and cognitive computing. The results show that implementing AI strategies can improve efficiency, accuracy and objectivity in HR management, as well as facilitate better communication and teamwork. However, challenges related to bias, privacy, and ethics also need to be considered. The implication of this research is the importance of considering the social and ethical implications of using AI technology in employee development, while continuing to explore new potential for improving performance and collaboration in the workplace.